Activities and Issues of Career Transition Program for Students with Learning Disabilities (SLD): An Initial Review - Rohaizat Ibrahim; Nabilah Abdullah; Mohd Hanafi Mohd Yassin; Ciptro Handrianto; Ahmet Serhat Uçar; Ary Kiswanto Kenedi (International Journal of Education, Information Technology, and Others, 2021)
Students with Learning Disabilities (SLD) have the equal rights to give services for improving their knowledge, skills, and attitudes for their future career. The aims of this study is to identify activities and issues of career transition program faced by students with learning disabilities in various situations. The method used in this study is qualitative by using conceptual approach as initial review several previous research. The study shows that several activities of career transition program have been conducted to prepare students with learning disabilities to working situation, such as (1) Psychometric exam; (2) Collaboration of stakeholders; (3) Program information; (4) Vocational education; and (5) Social relationships. Some issues have been highlighted related to career transition program, such as: (1) Career choices; (2) Experience; (3) Preference; (4) interest; and (5) Parent`s consideration. The conclusion of this study that it is needed the improvement in career transition program to provide opportunities to students with learning disabilities obtaining appropriate job. It is recommended to stake holders and policy maker to have a look the phenomena and issues related to career transition program. They should be more involved to find out the solution to carry out the quality life for students with learning disabilities.